Effectiveness of Digital Marketing on Revisit Intention Outpatient of Brebes Regional General Hospital - Shella Vina Putri; Endang Ruswanti; Rokiah Kusumapradja (Jurnal sosial dan sains, 2023)
Background: The Covid-19 outbreak turned into a pandemic in Indonesia in 2020. The patient's intention to visit the hospital due to the pandemic but can be influenced by the hospital's marketing strategy. Brebes Regional General Hospital before the Covid-19 pandemic used conventional marketing and, in an effort, to increase the number of repeat visits to patients in the pandemic era and industry 5.0, namely through the most effective marketing strategy, namely digital marketing. Purpose: The aim is to determine the influence and effectiveness of digital marketing in terms of people, physical evidence, process and promotion on the intention to revisit outpatients at Brebes Regional General Hospital. Methods: Using the Quasi Experimental Pre and postest method in digital groups and conventional groups and the Logistic Regression method. Results: The results showed that there was a difference and there was effectiveness in the digital marketing group on the promotion variable (0.45), process (0.56), physical evidence (0.37) and intention (0.54). There is a difference and effectiveness in the conventional group on the process variable (0.35). There is a simultaneous influence of 4P variables on the intention to revisit by 70.5%. Conclusion: There is a difference and effectiveness in patient re-visits in the outpatient service of the Brebes Regional General Hospital before and after the digital marketing intervention group on the variables of Promotion, Process, Physical Evidence and Visit Intention.